2013
DOI: 10.2478/s13380-013-0139-9
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin is neuroprotective through glutamate receptor-independent mechanisms in staurosporine-induced apoptosis of cultured rat cerebellar neurons

Abstract: The anticonvulsants that are currently available modulate the activity of neuronal receptors and ion channels, which are equally involved in apoptotic pathways. We investigated the hypothesis that gabapentin (GP), an anticonvulsant without effect on glutamate receptors acting as GABA analog, has neuroprotective properties. For comparison, we chose topiramate (TPM), which has been reported to be neuroprotective via AMPA receptors blockade. For this purpose, we used rat cerebellar granule neuron (CGN) cultures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It is possible therefore that multiple mechanisms are responsible for the anticonvulsant, anxiolytic, neuroprotective (Baydas et al, 2005) and antinociceptive activity observed in different animal models. In the context of the GBP effect on thermal hypoalgesia, a neuroprotective action mediated by glutamate receptorindependent mechanisms has been reported (Popescu et al, 2013). There is also evidence that GBP improves nerve remyelination after chronic sciatic nerve constriction injury (Câmara et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible therefore that multiple mechanisms are responsible for the anticonvulsant, anxiolytic, neuroprotective (Baydas et al, 2005) and antinociceptive activity observed in different animal models. In the context of the GBP effect on thermal hypoalgesia, a neuroprotective action mediated by glutamate receptorindependent mechanisms has been reported (Popescu et al, 2013). There is also evidence that GBP improves nerve remyelination after chronic sciatic nerve constriction injury (Câmara et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of α2δ-1 transmitted signalling also influences apoptotic cell death, anatomic reorganization, excitatory synaptogenesis, astrocytosis, and network hyperexcitability in a model of insultinduced cortical malformation (12). Recent studies revealed that gabapentin protects cultured neurons from staurosporine-induced apoptosis, and reduces the intensity of reactive gliosis, both in microglial and astroglial cells (13). Gabapentin has also been found beneficial in the treatment of alcohol withdrawal in alcoholics (14,15) and has a selective action in decreasing the convulsive and anxiety related signs of ethanol withdrawal in mice (16).…”
Section: Introductionmentioning
confidence: 99%